2021
DOI: 10.2147/cmar.s315511
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Notch4 in Cancer: Molecular Mechanisms and Therapeutic Perspectives

Abstract: The dysregulation of Notch signaling is found in many cancers and is closely related to cancer progression. As an important Notch receptor, abnormal Notch4 expression affects several tumor-cell behaviors, including stemness, the epithelial-mesenchymal transition, radio/chemoresistance and angiogenesis. In order to inhibit the oncogenic effects of Notch4 activation, several methods for targeting Notch4 signaling have been proposed. In this review, we summarize the known molecular mechanisms through which Notch4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
(205 reference statements)
0
13
0
Order By: Relevance
“…NOTCH4: The functions of NOTCH4 differ in different types of cancer. The overexpression of NOTCH4 is regarded as a poor prognosis marker in some scenarios 618 , while in others, it is considered a favorable marker 619 . There are no mature drugs targeting NOTCH4.…”
Section: Notch-targeted Therapiesmentioning
confidence: 99%
“…NOTCH4: The functions of NOTCH4 differ in different types of cancer. The overexpression of NOTCH4 is regarded as a poor prognosis marker in some scenarios 618 , while in others, it is considered a favorable marker 619 . There are no mature drugs targeting NOTCH4.…”
Section: Notch-targeted Therapiesmentioning
confidence: 99%
“…NOTCH4 expression was significantly higher in breast cancer patients compared to normal (Figure 4). Most studies suggested that NOTCH4 is abnormally overexpressed during cancer development and is involved in the regulation of several tumor-cell behaviours, mainly in stem cell-like self-renewal, epithelial-mesenchymal transition (EMT), radio-/chemo resistance and angiogenesis (Wu et al 2014;Lin et al 2016;Wu et al 2018;Shaik et al 2020;Xiu et al 2021). In contrast to C-JUN and NOTCH4, the expression of CTNND1 was significantly lower in breast cancer patients (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting C-JUN in adenocarcinomic human alveolar basal epithelial cells (A549) exhibits antiangiogenic activity in vitro and in vivo through exosome/miRNA-494-3p/PTEN signalling pathway (Shao et al 2021). Overexpression of NOTCH4 is reported in cancer development and is involved in EMT, angiogenesis and even radio-/ chemo resistance (Xiu et al 2021). In breast cancer, RNA-binding protein (RBP) DCAF13 induces NOTCH4 overexpression by inhibiting the activation of the E3 ubiquitin-protein ligase DTX3 that prevents NOTCH4 degradation (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Notch4 signaling not just affects tumor cell biological behaviors but also is responsible for tumor angiogenesis ( Xiu et al, 2021 ). Interestingly, our data demonstrated a similar result that Notch4 showed positive staining both in tumor cells and endothelial cells, suggesting Notch4 may play dual roles respectively in tumor cells and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%